Peculiarities of pre-competition emotional state of the Lithuanian national kayak and canoe rowing team members and junior kayakers and canoeists - Alekrinskis, A.; Bulotiene, D.; Dagyte, R. (Sporto Mokslas-Sport Science, 2019)
The pre-competitive state of an athlete is dependent on an athlete`s psychological preparation. Pre-competitive emotional state is a condition that occurs in athletes about two weeks prior to the competition and continues until it begins (Malinauskas, 2010). The pre-competitive state manifests itself for each athlete individually, and the manifestation of this state depends on the significance of the race, the competitor`s capacity, the quality of organizing the match, the coach and other important human behavior patterns as well as the individual characteristics of an athlete. In order to achieve the best sporting results, research must be carried out to find out if athletes are properly prepared for the intended race, what is their pre-competitive emotional state.Research discussion and conclusions. The questionnaire survey and the result analysis of the SAN test revealedthat the pre-competitive state of members of the Lithuanian national kayak and canoe rowing team did not differ statistically from the state of junior kayakers and canoeists (p > 0.05). However, a high level of pre-competitive emotional state (77%) dominated among members of the Lithuanian national kayak and canoe rowing team as compared to junior rowers when slightly more than half of the athletes had an average level of emotional state before the competition (54%). This means that the members of the Lithuanian kayak and canoe rowing team did not have a negative impact on their state during the competition and they felt better than junior kayakers and canoeists.Differences in well-being and mood between the Lithuanian kayak and canoe rowing team members and young kayakers and canoeists were not statistically significant (p > 0.05), but the activity of both groups appeared to be statistically significant (p < 0.05). The activity of elite Lithuanian kayakers and canoeists was higher than that of young kayak and canoe rowers. The situational and personal anxiety of Lithuanian kayak and canoe rowing team members and junior kayakers and canoeists was not statistically significant (p > 0.05).